The Design Theory Nexus - Pries-Heje, J.; Baskerville, Richard (MIS Research Centre, 2008)
Managers frequently face ill-structured or “wicked” problems. Such problems are characterized by a large degree of uncertainty with respect to how the problem should be approached and how to establish and evaluate the set of alternative solutions. A design theory nexus is a set of constructs and methods that enable the construction of models that connect numerous design theories with alternative solutions. It thereby offers a unique problem-solving approach that is particularly useful for addressing ill-structured or wicked problems. For each alternative solution in a design theory nexus one or more unique criteria are established to formulate a specific design theory. We develop a general method for constructing a design theory nexus and illustrate its utility using two field studies. One develops and applies an organizational change nexus. The other develops and applies a user involvement nexus. Each is a specific instantiation of the general design theory nexus constructs. Usingthese illustrations, we provide examples of how to evaluate